2022
DOI: 10.1002/hbm.25827
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity associated with familial risk for mental illness: A meta‐analysis of diffusion tensor imaging studies in relatives of patients with severe mental disorders

Abstract: Schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD) are heritable conditions with overlapping genetic liability. Transdiagnostic and disorderspecific brain changes associated with familial risk for developing these disorders remain poorly understood. We carried out a meta-analysis of diffusion tensor imaging (DTI) studies to investigate white matter microstructure abnormalities in relatives that might correspond to shared and discrete biomarkers of familial risk for psychotic or moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“… 57 A meta-analysis of white matter correlates of relatives of patients with severe mental disorders (MDD, bipolar disorder, and/or schizophrenia) showed decreased FA in the genu and splenium of the corpus callosum in relatives of patients as compared to controls, although a specific effect size was not reported. 56 Lim et al 54 concluded, in a meta-analysis, that history of childhood maltreatment was associated with reduced FA in the anterior corpus callosum, along with the fornix, anterior thalamic radiation, optic radiations, the inferior longitudinal fasciculus, and inferior frontal-occipital fasciculus. Notably, these regions are similarly implicated in MDD in our current systematic review.…”
Section: Discussionmentioning
confidence: 99%
“… 57 A meta-analysis of white matter correlates of relatives of patients with severe mental disorders (MDD, bipolar disorder, and/or schizophrenia) showed decreased FA in the genu and splenium of the corpus callosum in relatives of patients as compared to controls, although a specific effect size was not reported. 56 Lim et al 54 concluded, in a meta-analysis, that history of childhood maltreatment was associated with reduced FA in the anterior corpus callosum, along with the fornix, anterior thalamic radiation, optic radiations, the inferior longitudinal fasciculus, and inferior frontal-occipital fasciculus. Notably, these regions are similarly implicated in MDD in our current systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) has consistently identified measures indicative of decreased fiber integrity throughout the brain of those with ASD (Conti et al, 2017; Groen, 2011; Libero et al, 2016). However, decreased fiber integrity is associated with many other neurodevelopmental and psychiatric diagnoses and may simply be a non-specific indicator of global perturbation (Benedetti et al, 2014; Stojanovski et al, 2019; Xu et al, 2022). Increased cortical hemispheric symmetry appears to be more specific to ASD but has proven difficult to replicate (Carper et al, 2016; Deng & Wang, 2021; Postema et al, 2019; Sha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high level of comorbidity of psychotic and affective symptoms across both disorders [3][4][5][6][7][8]. Common DNA variants and brain changes that appear to influence the risk of both schizophrenia and bipolar disorder have been identified [9,10], and an individual's risk of suffering from either schizophrenia or bipolar disorder is elevated if a firstdegree relative has one of the disorders [11], indicating a significant overlap in genetic factors underlying the two disorders [12]. Therefore, it would be of theoretical and clinical value to examine similarities and differences in psychological processes across disorders [13,14].…”
Section: Introductionmentioning
confidence: 99%